Utilization of polarized microscopy to differentiate deep penetrating nevus from equine type melanomas. (16th February 2016) - Cleaver, Nathan; Parikh, Kruti; Kazlouskaya, Viktoryia; Elston, Dirk
Abstract : Equine type melanoma can mimic deep penetrating nevus (DPN), making histologic diagnosis challenging. We sought to investigate if the pattern of collagen polarization could be helpful in this setting. A total of 52 specimens were reviewed with polarized microscopy to determine whether refractile collagen was present within melanocytic nests vs. surrounding but not within the nests. Seven of eight (87.5%) equine type melanomas demonstrated refractile collagen within melanocytic nests in part or all of the lesion. In contrast, DPN showed no refractile collagen within the melanocytic nests. Instead, 12 (100%) DPNs and 14 of 16 (87.5%) common combined nevi (DPN plus banal nevus) demonstrated refractile collagen only surrounding melanocytic nests. The entrapment of refractile collagen, as seen with polarized microscopy, within melanocytic nests can support a diagnosis of equine type melanoma.